The effects of new consumption spaces to their environs in the process of constituting urban value - Topçu, Kadriye (Deniz); Topçu, Mehet (Efekty nowych przestrzeni konsumpcji w procesie tworzenia wartości miejskiej, 2011)
The cities begin to give priority to large-scale urban projects to bring themselves to the fore and to attract the capital. One of the main uses of these projects involves shopping centers which guide the development of urban spaces, increase the prestige of districts in which they are located and provide display areas. Although these centers are built as architectural solutions, they have a great impact on the process of change and transformation of urban spaces and thus on urban planning. This paper analyses the effects of these consumption spaces − shopping centers on their environs in terms of environmental and economical values. In the scope of the study, M1 Tepe-Real Shopping Center and its environs in Konya were selected as a sample area. In conclusion it is observed that the selected shopping center has mainly an economic impact on its environs
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 195, s. 171-178
Keywords: consumption space; shopping centers; town planning design